Hospital Level Characteristics Associated with Clostridium difficile Rates and Outcomes. - Sanchez, Edgar. (2017)
Abstract: The incidence of Clostridium difficile infection (CDI) has increased steadily during the past fifteen years. Previous studies have shown that CDI rates and outcomes vary among hospitals with different characteristics though none of these studies adjusted for the patient case mix. We used data from the Nationwide Inpatient Sample (NIS), which is part of the Healthcare Cost and Utilization Project (HCUP), from the years 2003 to 2012 for this cross sectional study. We compared the odds of a CDI diagnosis and secondary outcomes of CDI, including in-hospital case fatality, duration of hospitalization, and total hospital charges, according to different hospital characteristics - which included location, teaching status, size, multi-hospital membership status, and number of ancillary staff. All statistical models were adjusted for patient characteristics, including age, sex, the expected primary payer, socioeconomic status, and comorbidities. Our study population consisted of 58% females with an average age of 47.9 (SD ± 27.9) years. There were 644,765 patients with a CDI diagnosis, of which 450,257 were considered to have secondary CDI. Patients who were admitted to urban as compared with rural hospitals had an increased odds of having a CDI diagnosis (adjusted OR 1.53, 95% CI 1.45, 1.61), increased odds of in-hospital death with CDI (adjusted OR 1.36, 95% CI 1.29, 1.42), a longer duration of hospitalization for patients with CDI by 46% (95% CI 43%, 49%) and an increase in total charges for patients with CDI by 84% (95% CI 75%, 93%). Teaching hospitals when compared with nonteaching hospitals were also associated with an increased odds of CDI (adjusted OR 1.21, 95% CI 1.16, 1.26), in-hospital death with CDI (adjusted OR 1.12, 95% CI 1.08, 1.16), increase in duration of hospitalization for CDI by 12% (95% CI 10%, 13%) and an increase in total hospitalization charges for CDI by 9% (95% CI 7%, 11%). The Northeast had significantly higher rates of CDI, CDI case fatality, duration of hospitalization for CDI, and amount of total charges when compared to other regions of the country. Multi-hospital membership status was found to be significantly associated with the duration of hospitalization. We also found significant associations between CDI rates and outcomes with several nursing categories. There was significant variation in CDI rates and outcomes for hospitals based on location, teaching status, region, and hospital classification, even after adjusting for patient-level characteristics.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: David Snydman.; Committee: Shira Doron, John Wong, Matthew Finkelman, and Jennifer Chow.; Keywords: Health sciences, and Epidemiology.